Analysis of the Wa’d Ijarah Muntahiyah Bi al-Tamlik (IMBT) Contract From the Perspective of Islamic Law and Indonesian Civil Law - Suprapdi (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Akad Ijarah Muntahiyah Bi al-Tamlik (IMBT) is a lease agreement that ends with the transfer of property rights by way of sale and purchase or grants at the end of the lease period. The ijarah contract and the sale and purchase contract are connected with a promise. Based on the DSN-MUI fatwa number: 27/DSN-MUI/III/2002 concerning IMBT, the promise (wa'ad) is non-binding, thus causing legal uncertainty for LKS and customers. Then the DSN-MUI issued a fatwa number: 85/DSN-MUI/XII/2012. Then the promise (wa'ad) in the IMBT contract became binding (mulzim). Of course, this has an impact on the occurrence of ta'alluq risk and has the potential to meet conditional buying and selling. This research uses normative juridical methods with a statutory and conceptual approach. The results of the analysis show that the legal status of fulfilling promises (wa'ad) in every Sharia transaction and business is binding (mulzim) and has caused many benefits for the Islamic economic community, such as legal certainty and guaranteed contract continuity, especially in the IMBT contract. Viewed from the point of view of Indonesian Civil Law, IMBT contracts or contracts are included in non-named agreements. This is contained in Article 1319, which arises from the principle of freedom of contract (Article 1338), and IMBT contracts also meet the requirements of valid agreements as contained in Article 1320 of the Civil Code and the legal consequences caused by IMBT contracts, namely rights and obligations.